Cover Picture: Decarboxylative Sulfinylation Enables a Direct, Metal‐Free Access to Sulfoxides from Carboxylic Acids (Angew. Chem. Int. Ed. 43/2022). Issue 43 (18th October 2022) - Nguyen, Viet D.; Haug, Graham C.; Greco, Samuel G.; Trevino, Ramon; Karki, Guna B.; Arman, Hadi D.; Larionov, Oleg V.
Abstract : Decarboxylative sulfinylation is reported by Oleg V. Larionov and co‐workers in their Research Article (e202210525 ), as illustrated in the cover picture. The reaction is enabled by radicalophilic reactivity of the sulfinyl sulfones shown in the top left that is distinct from the known dissociation and nucleophilic substitution pathways. Given the importance of carboxylic acids and sulfoxides for medicinal chemistry, agroscience, and organic synthesis, decarboxylative sulfination addresses the unmet need for a direct interconversion between the two functional groups and provides access to new sulfoxide chemical space.